Filozofia jako poszukiwanie wiecznego bytu i ponadczasowej mądrości - Wadowski, Jan (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
In the first introductory part of the article, I discuss the contemporary paradigmin philosophy, which tends to avoid addressing some crucial subjects and issues. It seems that contemporary philosophy surrenders to the paradigm of promissorymaterialism, dominant in the particular sciences, whereas searching for the eternalshould be the main task of the love of wisdom.In the second part of the article I focus on the issue of eternity, being inspired by theworks of such authors as: A. Huxley, P. D. Uspienski, L. Kołakowski, M. Kojfman,R. Sheldrake, M. Beauregard, B. Griffiths and P. van Lommel. The eternal dimension isreal and it is expressed in the spiritual aspirations. To achieve them certain practise isnecessary to discover what is non-dual (such ideas may be found i.e. in the PatanjaliYoga). In the paper, I assume that the direct contemplation of truth is possible and it requiresintegration of the inner attitude and the external exercises (spirit and body), mindand intuition, rationality and spirituality.